Agricultural R&D in Uruguay: policy, investments, and institutional profile - Beintema, Nienke M.; Hareau, Guy; Bianco, Mariela; Pardey, Philip G. (International Food Policy Research Institute, 2000)
Although Uruguay has only a small number of agricultural R&D agencies, the intensity with which the country invests in agricultural R&D is comparatively high, especially by developing-country standards. In 1996 total agricultural R&D expenditure as a share of agricultural GDP was 1.7 percent.